Potential role of milk fat globule membrane in modulating plasma lipoproteins, gene expression, and cholesterol metabolism in humans: a randomized study. Issue 1 (27th May 2015) - Rosqvist, Fredrik; Smedman, Annika; Lindmark-Månsson, Helena; Paulsson, Marie; Petrus, Paul; Straniero, Sara; Rudling, Mats; Dahlman, Ingrid; Risérus, Ulf
ABSTRACT: Background: Butter is rich in saturated fat [saturated fatty acids (SFAs)] and can increase plasma low density lipoprotein (LDL) cholesterol, which is a major risk factor for cardiovascular disease. However, compared with other dairy foods, butter is low in milk fat globule membrane (MFGM) content, which encloses the fat. We hypothesized that different dairy foods may have distinct effects on plasma lipids because of a varying content of MFGM. Objective: We aimed to investigate whether the effects of milk fat on plasma lipids and cardiometabolic risk markers are modulated by the MFGM content. Design: The study was an 8-wk, single-blind, randomized, controlled isocaloric trial with 2 parallel groups including overweight men and women ( n = 57 randomly assigned). For the intervention, subjects consumed 40 g milk fat/d as either whipping cream (MFGM diet) or butter oil (control diet). Intervention foods were matched for total fat, protein, carbohydrates, and calcium. Subjects were discouraged from consuming any other dairy products during the study. Plasma markers of cholesterol absorption and hepatic cholesterol metabolism were assessed together with global gene-expression analyses in peripheral blood mononuclear cells. Results: As expected, the control diet increased plasma lipids, whereas the MFGM diet did not [total cholesterol (±SD): +0.30 ± 0.49 compared with −0.04 ± 0.49 mmol/L, respectively ( P = 0.024); LDL cholesterol: +0.36 ± 0.50 compared with +0.04 ± 0.36 mmol/L, respectively ( P = 0.024); apolipoprotein B:apolipoprotein A-I ratio: +0.03 ± 0.09 compared with −0.05 ± 0.10 mmol/L, respectively ( P = 0.007); and non-HDL cholesterol: +0.24 ± 0.49 compared with −0.14 ± 0.51 mmol/L, respectively ( P = 0.013)]. HDL-cholesterol, triglyceride, sitosterol, lathosterol, campesterol, and proprotein convertase subtilisin/kexin type 9 plasma concentrations and fatty acid compositions did not differ between groups. Nineteen genes were differentially regulated between groups, and these genes were mostly correlated with lipid changes. Conclusions: In contrast to milk fat without MFGM, milk fat enclosed by MFGM does not impair the lipoprotein profile. The mechanism is not clear although suppressed gene expression by MFGM correlated inversely with plasma lipids. The food matrix should be considered when evaluating cardiovascular aspects of different dairy foods. This trial was registered at clinicaltrials.gov as NCT01767077.